Visit of Prime Minister Dr. Manmohan Singh to Japan 13-16 December 2006. - Manmohan Singh 1932-; India. Ministry of External Affairs. Public Diplomacy Division (New Delhi Public Diplomacy Division, Ministry of External Affairs, Government of India, 2007)
Transcript of speeches delivered during his Japan visit.
Keywords: Manmohan Singh -- 1932- -- Travel -- Japan; Visits of state -- Japan; India -- Foreign relations -- Japan; Japan -- Foreign relations -- India